Dynamics of Contemporary Indonesian Sufism: Actors, Scientific Genealogy, Educational Patterns, and Doctrines of the Majelis Shalawat in East Java - Rubaidi Rubaidi (Kawanua International Journal of Multicultural Studies, 2020)
This article examines the dynamics of Majelis Shalawat as a “new” Sufi institution that flourished in the late 20th and early 21st centuries. Majelis Shalawat as another alternative to the tarekat is another option for the community because it teaches various dimensions of truth and makrifat. This following research focused on 3 (three) Majelis Shalawat, they are: (1) Majelis Shalawat Kubro (Gus Syamsu Dhuha), (2) Majelis Shalawat Muhammad (Gus Kahar), and (3) Majelis Shalawat Adlimiyah (Gus Mursyidin) in East Java. These are being an interested attention due to its multiple findings; Firstly, having a teacher backrest that forms a scientific genealogy. The three murshids become one unity because there is a key figure beyond them, namely KH. Muhammad Tamyiz (Mbah Tamyiz). Mbah Tamyiz connected with Sufi scholars from the 1970s to 1980s who were continued by his three successors. Secondly, it is built based on a specific Sufi education pattern, namely the strict mujahadah and riyad traditions. Thirdly, on the basis of scientific genealogy and educational patterns, which finally forming doctrines or thoughts. The doctrine taught by the three murshids, both stated and unstated, is continued with Abu Yazid al-Bustami (ittihad), Mansur al-Hallaj (hulul), Ibn al-'Arabi (wihdat al-Wujud), until Abdul Karim al-Jilli (tajalli). As a preliminary study, this article attempts to present the relationship among the scientific genealogy, educational patterns, and doctrines of the teachings of the three murshids in their respective of Majelis Shalawat as a part of contemporary Indonesian Sufi